Women’s Empowerment with Islamic Philanthropy Model: A Case Study of STF Dompet Dhuafa Program in South Sulawesi - Nurfiah Anwar; Syarifuddin Syarifuddin (Department of Islamic Economics, Islamic University of Indonesia, 2021)
Women are the main poverty insurers of the family because women have to think about their survival and family, but to get out of the condition of poverty women are still limited access to get loan funds to improve their standard of living, in addition to patriarchal cultural motives that dominate society in general as well as government programs that are still gender biased. Women have proven to be able to quickly adapt to weak economic conditions and still be able to think under economic crisis. The purpose of this research is to understand women's empowerment through the STF program held by Dompet Dhuafa and its mechanisms. The type of research used is a type of qualitative research that describes the results of research through sitematic writing with a phenomenological approach by observing phenomena that occur. The data source is obtained from primary data in the form of interviews to the Dhuafa Wallet and secondary data in the form of literature obtained from the internet and print media. The authors see from the results of the study that the STF program is able to empower women well.